A 3 year old girl presented with abdominal distention since birth with developmental delay - Nahar, Luthfun; Karim, A. S. M. Bazlul; Biswas, Subir Ananda; Mondal, Mohuya; Dey, Bishnu Pada (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: A 3 year old girl, 3rd issue of consanguineous parents from the Feni District (south part of Bangladesh) immunized as per EPI schedule presented at the outpatient department with the history of progressive abdominal distension and not growing well since birth. She had also the history of developmental delay and recurrent respiratory tract infection. Still she can not stand without the support and unable to make a sentence completely. Her brother died at 5 months of age with abdominal distention with unknown cause. She had no history of jaundice, hematemesis, melena, convulsion and craving for food.